2017
DOI: 10.1016/j.envres.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal mercury exposure, neurodevelopment and apolipoprotein E genetic polymorphism

Abstract: The aim of the present study was to evaluate the association between prenatal exposure to mercury (Hg) and neurodevelopment of the child, taking into account genetic polymorphism of apolipoprotein E (Apoe) and other relevant confounders. Six hundred and one mother-child pairs were recruited from the central Slovenia region and 243 from Rijeka, on the Croatian coast of the northern Adriatic. The total Hg in cord blood, Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) assessment at 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…(Skröder et al, 2015) and Poland (mean of Se in serum at the first trimester of pregnancy: 48.3 µg/L) (Polanska et al, 2016(Polanska et al, , 2017. Additionally, a positive, but only marginally significant, association was observed between cord blood Se serum (geometric mean of 40.1 ng/g) and the language domain among children who were non-carriers of the ε4 allele for the apolipoprotein E gene, but not in the ε4 carriers (Snoj Tratnik et al, 2017). This ε4 allele was also found to be a modifier of the association between mercury and cognitive performance in the same population, the carrier children being the ones who obtained poorer scores.…”
Section: Discussionmentioning
confidence: 84%
“…(Skröder et al, 2015) and Poland (mean of Se in serum at the first trimester of pregnancy: 48.3 µg/L) (Polanska et al, 2016(Polanska et al, , 2017. Additionally, a positive, but only marginally significant, association was observed between cord blood Se serum (geometric mean of 40.1 ng/g) and the language domain among children who were non-carriers of the ε4 allele for the apolipoprotein E gene, but not in the ε4 carriers (Snoj Tratnik et al, 2017). This ε4 allele was also found to be a modifier of the association between mercury and cognitive performance in the same population, the carrier children being the ones who obtained poorer scores.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, AD and Hg intoxication have a common risk factor in the gene encoding the apolipoprotein E (ApoE). Hg exposure typically produces worse outcomes in individuals with the ApoEε4 allele [170][171][172][173], and this allele is linked also to an increased probability of developing AD [8][9][10][11]14]. The underlying reasons for this similar risk factor are unclear, however, and a number of explanations have been proposed [8,174], including the possibility that the beneficial ApoE variants may interact with and promote clearance of the Aβ peptide [175] or Hg ions [9,11].…”
Section: Biological Relevance and Other Molecular Effects On Ad Involmentioning
confidence: 99%
“…Still, this limit is based on acute outbreaks such as those in Minamata and Iraq; some studies have shown in recent years that exposure to relatively low levels of methylmercury (below the WHO limit) have the potential to cause additional long-term consequences such as genotoxicity (9,(23)(24)(25). Although recent studies on AD patients or older individuals have failed to find correlations between the content of mercury and neurodegenerative processes (2,26), chronic neurodegeneration due to chronic methylmercury exposure may be better associated with longitudinal assessments of mercury levels (7,(11)(12)(13)(14)(15)(16).…”
Section: Mercury: a Worldwide Concernmentioning
confidence: 99%